Pemberdayaan Peer Modeling untuk Manajemen Diri Lansia Hipertensi - Rohmawati, Zubaida; Suryani, Suryani; Khasanah, Istiqomah Nur (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Hypertension in the elderly in Bedog Hamlet, Sleman, is a health problem that requires optimal self-management, but is hampered by the low knowledge of cadres and minimal participation of Posyandu (Integrated Health Post) members. This program aims to empower cadres and the elderly as peer models to strengthen hypertension self-care management. Using a Community-Based Participatory Research (CBPR) approach, the team trained seven cadres and five selected elderly with hypertension through intensive sessions that included role-playing and participatory discussions. Evaluation showed a significant increase in cadre knowledge, with the average score increasing from 58.6 to 81.4. The success of this training was followed up by the formation of active peer models and demonstrated increased self-efficacy. Peer model involvement in Posyandu activities was positively correlated with increased elderly attendance. Therefore, empowering peer modeling is an effective and feasible strategy to increase community resource capacity and motivate the elderly in managing hypertension through creating a supportive social environment.